Strategi Efektif untuk Mengurangi Tingkat Pengangguran - Rahmawati, Kurnia (Maliki Interdisciplinary Journal, 2024)
Unemployment is a complex socio-economic problem that has a major impact on the economic growth and welfare of a country’s people. This article investigates various approaches that have proven effective in reducing unemployment rates in various situations. This study analyzes the latest literature and case studies to identify five main strategies: (1) improving the quality of vocational education and training in accordance with the needs of the job market; (2) implementing fiscal and monetary policies that encourage job creation; (3) building programs and support for entrepreneurship and MSMEs; (4) investing in infrastructure and labor-intensive sectors; and (5) labor market reform. The results show that a combination of different strategies can significantly lower the unemployment rate if implemented locally. In addition, this article discusses the problems that arise when implementing these strategies. To achieve optimal results, he suggests a broader approach that involves cooperation between the private sector, civil society, and government.